The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/aenm.201702533
|View full text |Cite
|
Sign up to set email alerts
|

All‐Oxide MoOx/SnOx Charge Recombination Interconnects for Inverted Organic Tandem Solar Cells

Abstract: Multijunction solar cells are designed to improve the overlap with the solar spectrum and to minimize losses due to thermalization. Aside from the optimum choice of photoactive materials for the respective sub‐cells, a proper interconnect is essential. This study demonstrates a novel all‐oxide interconnect based on the interface of the high‐work‐function (WF) metal oxide MoOx and low‐WF tin oxide (SnOx). In contrast to typical p‐/n‐type tunnel junctions, both the oxides are n‐type semiconductors with a WF of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…An example was provided by Bag et al in 2016, where they used an ICL made of evaporated chromium and molybdenum oxide . Only in 2018, Becker et al reported the first all‐oxide ICL for polymer tandem solar cells . A possible reason for the scarcity of such examples might be because very few metal oxide layers guarantee the protection of the front cell active layer against the processing from solution of the back cell active layer .…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…An example was provided by Bag et al in 2016, where they used an ICL made of evaporated chromium and molybdenum oxide . Only in 2018, Becker et al reported the first all‐oxide ICL for polymer tandem solar cells . A possible reason for the scarcity of such examples might be because very few metal oxide layers guarantee the protection of the front cell active layer against the processing from solution of the back cell active layer .…”
Section: Tandem Solar Cellsmentioning
confidence: 99%
“…Also sol–gel tin oxide has been used for organic photovoltaic devices . Recently, Becker et al presented a tandem polymer solar cell with a molybdenum oxide/tin oxide ICL, where these layers were deposited by thermal evaporation and atomic layer deposition, respectively. Here we demonstrate the use of commercially available tin oxide colloidal dispersions as ETL for the solution‐processing of efficient single junction and tandem polymer solar cells with both the inverted and the conventional configuration.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several different combinations of materials have been proposed as ICL, involving either organic materials or transparent semiconducting metal oxides . For the selective extraction of holes from the photoactive layers poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is widely used but also metal oxides such as MoO 3 , V 2 O 5 , and WO 3 , or graphene oxide (GO) can be used for the purpose.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several different combinations of materials have been proposed as ICL, involving either organic materials or transparent semiconducting metal oxides. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] For the selective extraction of holes from the photoactive layers poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is widely used but also metal oxides such as MoO 3 , [25] V 2 O 5 , [26] and WO 3 , [27] or graphene oxide (GO) [28] can be used for the purpose. For selective electron extraction, solution-processed metal oxides such as ZnO nanoparticles, [29] sol-gel TiO x , [11] or Lidoped ZnO [30] are popular.…”
mentioning
confidence: 99%